الحماية الجنائية الموضوعية للصحة العامة (دراسة تحليلية) - سعيد, زانا رفيق; صادق, زمن صلاح (Sulaimani Journal for Humanities, 2022)
Objective criminal protection is the one related to criminalization and punishment and protects public health by imposing illegality on behaviors that harm public health, meaning that every criminal rule determines the crime in an act and imposes a penalty on its perpetrator in order to protect public health, and to enter The Criminal Code undoubtedly emphasizes the importance of protecting public health, and the Iraqi legislator criminalized acts that harm public health in Chapter seven of Chapter seven under the title (Crimes of Public Danger), as well as criminalizing some acts in the Iraqi Consumer Protection Law No. (1)for the year 2010, as well as criminalizing acts that lead to pollution and directly affect public health. In the Environmental Protection and Improvement Law No. (27) for the year 2009 and the Law for the Protection and Improvement of the Environment for the Kurdistan Region of Iraq No. (8) for the year 2008. Accordingly, we will address in this research the statement of crimes that harm public health and the penalties for the persons who commit them, following the descriptive analytical method, according to what is included in the Iraqi Penal Code and the mentioned special laws.